ELASTIC SYMMETRY AND ANISOTROPIC PARAMETERS OF SPECIMENS OF ARCHEAN GNEISSES AND KOLA SUPERDEEP-BOREHOLE AMPHIBOLITES - Prodaivoda G.T.; Aleksandrov K.S. (My University, 1998)
Using an invariant-polarization ultrasound method, we have studied the velocities of elastic waves in the gneisses and amphibolites of the second rock mass of the Archean complex of the Kola superdeep borehole (7622-9456 m) and calculated the determinate components of acoustic tensor and elastic-constant tensor and their symmetry. The symmetry of the studied structures is shown to be rhombic and triclinic. The stereoprojections of mineral's crystallographic orientation and normals to microfractures are built by the data on the inversion of the azimuthal dependence of elastic constants.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей